Mainamati - Shamsul Alam, A. K. M. (Dept. of Archaeology and Museums, Cultural Affairs and Sports, Ministry of Information and Broadcasting, Govt. of the People's Republic of Bangladesh, 1975)
On the history and antiquities of Mainamati, ancient city in Comilla District.